Unparalleled volatility in sector-wise return in the chittagong stock exchange: a covid-19 perspective / Nusrat Jahan and Mohammad Nayeem Abdullah - Jahan, Nusrat; Abdullah, Mohammad Nayeem (Universiti Teknologi MARA, 2021)
This study examined the effect of the Covid-19 health crisis on the volatility of sector-wise securities return listed in the Chittagong Stock Exchange (CSE) and compared this volatility with the pre-pandemic context. This study focused on the Chittagong Stock Exchange because this bourse offers a platform for negotiability and transferability of securities to investors in Chittagong and also plays a significant role in capital mobilization and the industrial development of Bangladesh. A sample of 90 securities under 19 sectors listed in the CSE were examined. The trend analysis indicated that Bank, Food, Footwear, Leasing, Life Insurance, Electrical and Engineering and Mutual Funds had same level of volatility between the Pre-Covid and Post-Covid time periods. Only four sectors, including Energy, Telecommunication, General Insurance and Miscellaneous sectors displayed a higher Post-Covid volatility relative to the Pre-Covid context. The result indicated that volatility of return was not the same for 19 sectors in the CSE over the selected time period. The researcher discovered that high and low periods of deaths had a significant impact on weekly volatility of return on 19 sectors of the CSE. However, the difference in volatility of return across all sectors between the Pre-Covid and Post-Covid time periods were not statistically significant from each other.